The Effectiveness of Terrorism Prevention Policy in the Special Region of the Capital of Jakarta (Study on Indonesian National Armed Forces and Indonesian Police as Pressure Organizations) - Usuluddin, Fachruddin; Riniwati, Harsuko; Marjono, Marjono; Istiqomah, Milda (Wacana Journal of Social and Humanity Studies, 2023)
The government's policy objectives for countering terrorism in the DKI Jakarta Province have not been effective. This is marked by the lack of a sense of security for some people in dealing with acts of terrorism carried out by government officials. Based on this phenomenon, the research problem is formulated, namely why the government has not met expectations in implementing counter-terrorism policies, to know what factors determine the effectiveness of the policy. The method used is MICMAC analysis. The data in this study were obtained from literature studies from related documents, journals, and other scientific articles. The variables in this study refer to 5 indicators of policy effectiveness indicators, broken down into eight variables: organization, environment, workers, management policies and practices, and technology in training education and training centers. Overall, the results of the study indicate that the implementation of counter-terrorism in the DKI Jakarta Province has not been effective. This can be seen from the regulation and control of the TNI (Indonesian Armed Forces) and Polri (Indonesian Police) apparatus as pressure organizations that have not been maximized. The lack of achievement of these goals is related to several factors, including internal factors (factors originating from within the organization) and external factors (factors originating from outside the organization). However, the government's efforts to prevent acts of terrorism continue as carried out by the TNI and Polri officers through training and training camps with community support. Keywords: effectiveness, counter-terrorism, external factors, internal factors, policy